Алгоритм управления объектом с компенсацией транспортного запаздывания - Жуков, С.Ф.; Важинский, А.И. (Технічна електродинаміка, 2012)
A study of control object - complex weight dosage that provides training materials smelting process. The study performed mathematical modeling of complex systems, the analysis of the obtained models. These theoretical results formed the basis for the implementation of complex subsystems weight.